BUDIAIA’S VERBAL ENHANCERS AT THE POETRY OF JURISTS & HERMITS IN UMAYYAD - BADAWI HAMAD AL-ZUHAIRI, JAMEEL; KAREEM DAWOOD, FATIMA (Journal of College of Education, 2019)
This research deals with the budaiyaia’s verbal enhancers in the poetry of jurists&hermits in the umayyad period like: (aljenas, backing the inability to the beginning in poetry, altasria and inlay, necessity what is unnecessary, excerption and imbedding ), which had an effective effect in conveying the meaning to the recipient clearly, and most of its meanings revolve around (advice, guidance, life and death) to prove us in the end the budaiyaia’s verbal enhancers, a prominent feature in their poetry can not be overlooked, It has come into service meanings, as that the Holy Quran, and the Prophet’s Hadith had a clear effect on their poetry to been tributary enrich their language, ideas and meanings.